Understanding by design : professional development workbook - McTighe, Jay.; Wiggins, Grant P., 1950- (Alexandria, VA : Association for Supervision and Curriculum Development, 2004)
Provides resources to educators in developing curriculum and assessments and includes templates for designing a unit or course, criteria for reviewing curricular designs, workshop activities, and graphic organizers.
Teacher Librarian.
Professional
Keywords: Comprehension; Curriculum planning -- United States; Curriculum-based assessment -- United States; Learning; Achievement tests -- United States; Apperception; Curriculum planning -- United States; Learning and scholarship